(untitled) (Educological discourse, 2014)
In the article analyzes approaches to solving the problem of professional training kindergarten teachers in Germany in the nineteenth century. Examined the concept of education of H. Schrader-Breyman; defined the basic principles of training future kindergarten teachers preschools to the profession; disclosed the requirements for professional competence of kindergarten teachers of preschool education; carried characterization of the professional activities of H. Schrader-Breyman to the field of education of preschool children and kindergarten teachers in character education in Germany.